Новый подвид круглоголовки-вертихвостки — Phrynocephalus guttatus kalmykus ssp. n. (Sauria, Agamidae) из Калмыкии - Бадмаева, В.И.; Щербак, Н.Н. (Вестник зоологии, 1983)
Phrynocephalus guttatus kalmykus ssp. n. is described from the European part of fhe species range. It s district by pholidosi peculiartics and by tail underside pattern. Zoogeographic importance of the Volga-Ural interfluve is emphasized.